Technology transfer, policies, and the role of the private sector in the global poultry revolution - Narrod, Clare; Pray, Carl E.; Tiongco, Marites (International Food Policy Research Institute, 2008)
With the Biotech Revolution, questions are being asked about what role the government should play in the process—does public research in developing countries play a role? Can governments speed the spread of technology by offering complementary services? Unlike the public investment–driven Green Revolution in cereals, the “Poultry Revolution” in developing countries was driven by the successful transfer of biological technology developed by the private sector in the developed world to developing countries. This paper uses a supply response function to measure the importance of different types of private technology and of public investments on poultry productivity. The findings confirm that imported private technology was important to the growth of the poultry industry but also emphasize the importance of complementary government investments such as veterinary services.